Mastery of STEM-Based Research Approach of Science Teachers In Jakarta - Gufron Amirullah; Irdalisa Irdalisa (STAI Hubbulwathan Duri, 2022)
The STEM approach is the right innovation developed at this time to improve the quality of science learning according to the needs of students in 21st century. The purpose of this study was to identify the mastery of STEM-based research approach of science teachers in Jakarta. The research subjects were elementary, middle and high school teachers in DKI Jakata, totaling 40 teachers. Sampling is done by purposive sampling technique. Technique and instrument for collecting data on mastery of STEM-based research approach of science teachers using multiple choice test. Data analysis using t-test using SPSS 20.The results showed that the value of sig (2-tailed) mastery of STEM-based research approach of science teachers (posttest) 0.05. It can be concluded that there is a difference in the average of themastery of STEM-based research approach of science teachersof the experimental class and control class.